All 3D printed energy harvester for autonomous and sustainable resource utilization. (October 2018) - Seol, Myeong-Lok; Ivaškevičiūtė, Rusnė; Ciappesoni, Mark A.; Thompson, Furman V.; Moon, Dong-Il; Kim, Sun Jin; Kim, Sung Jin; Han, Jin-Woo; Meyyappan, M.
Abstract: Despite rapid advances in 3D printing, fabrication of energy harvesters has not benefited much due to incompatible materials and fabrication processes for conventional energy conversion mechanisms and associated devices. In this work, an all 3D printed energy harvester is introduced based on the triboelectric mechanism. Grating disk type triboelectric nanogenerator (TENG) is fabricated by assembling the electrode layer, triboelectric layer and case package, all of which are made by 3D printing. Effects of various structural and material designs are evaluated. In particular, the order of electrification of representative printable materials is characterized to provide material selection guidelines. The all 3D printed TENG provides a root-mean-square (RMS) open-circuit voltage of 231 V, RMS short-circuit current of 18.9 μA, and maximum RMS power of 2.13 mW, which are sufficient to power general wireless electronic systems. The combination of 3D printing and energy harvesting realizes the ideal resource utilization strategy by implementing a sustainable energy device through a sustainable process. Graphical abstract: fx1 Highlights: An energy harvester, in which all components are made by 3D printing, has been implemented for the first time. The triboelectric mechanism has been adopted due to its excellent material and manufacturing compatibility with 3D printing. Triboelectric properties of representative 3D printing materials were experimentally analyzed.